Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1161/01.atv.0000115638.27381.97
|View full text |Cite
|
Sign up to set email alerts
|

Adipophilin Enhances Lipid Accumulation and Prevents Lipid Efflux From THP-1 Macrophages

Abstract: Objective-Uptake of modified low-density lipoprotein (LDL) by macrophages through scavenger receptors results in lipid droplets accumulation and foam cell formation. Excess lipid deposition in macrophages has been reported to modulate expression of several genes including adipophilin. In this study, we investigated the function of adipophilin in lipid accumulation and cholesterol efflux in THP-1 macrophages. Methods and Results-Adipophilin mRNA expression was 3.5-fold higher in human atherosclerotic plaques co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
144
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 54 publications
14
144
2
2
Order By: Relevance
“…ADRP is the most abundant and best characterized PAT protein in human and mouse macrophage-derived foam cells (Buechler et al, 2001;Larigauderie et al, 2004;Paul et al, 2008b). Interestingly, the expression of ADRP in the atherosclerosis-studded arteries of ApoE-deficient mice was approximately 3.5-fold higher than in the atherosclerosis-free arteries of wild-type mice (Paul et al, 2008b).…”
Section: Adrpmentioning
confidence: 99%
See 1 more Smart Citation
“…ADRP is the most abundant and best characterized PAT protein in human and mouse macrophage-derived foam cells (Buechler et al, 2001;Larigauderie et al, 2004;Paul et al, 2008b). Interestingly, the expression of ADRP in the atherosclerosis-studded arteries of ApoE-deficient mice was approximately 3.5-fold higher than in the atherosclerosis-free arteries of wild-type mice (Paul et al, 2008b).…”
Section: Adrpmentioning
confidence: 99%
“…Inactivation of the Adrp gene in ApoE-deficient mice significantly reduced the number of lipid droplets in the foam cells in atherosclerotic lesions and protected mice against atherosclerosis (Paul et al, 2008b). Moreover, overexpression of ADRP resulted in increased lipid droplet accumulation due to reduced cholesterol efflux from THP-1 macrophages (Larigauderie et al, 2004). In contrast, peritoneal macrophages isolated from © Higher Education Press and Springer-Verlag Berlin Heidelberg 2012…”
Section: Adrpmentioning
confidence: 99%
“…[60][61][62] ADRP is a member of the PAT family (Perilipin, ADRP, TIP47) of proteins and plays an important role in adipocyte differentiation, lipolysis modulation, lipid body assembly and biogenesis (reviewed in ref. 63).…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…Increased ADRP expression by itself has been shown to be directly related to the enhanced capacity of neutral lipid storage, as ADRP promotes triglycerides and cholesterol storage and reduces cholesterol efflux. 60 ADRP may act also as a nucleation center for the assembly of lipids to form nascent lipid bodies and to enhance droplet stability upon lipolytic conditions. 64,65 In accordance, Kjerrulf et al, showed reduced cholesterol accumulation in ob/ob mouse macrophages.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%
“…ADFP is an intracellular protein that associates with intracellular lipid droplets in adipocytes, monocytes, and macrophages and is thought to facilitate the accumulation of cholesterol esters from acetylated low-density lipoprotein (26,27). Gene expression profiling showed that ADFP is expressed in higher quantities at baseline in lps high than lps low individuals (Table VI), suggesting that increased ADFP expression marks a cell that is predisposed to produce higher amounts of LPS-induced cytokines and that ADFP may have a functional effect on LPS-induced cellular responses.…”
Section: Role Of Adfp In Lps-induced Mcp-1 Mrna Productionmentioning
confidence: 99%